Kinase inhibitors of the IGF-1R as a potential therapeutic agent for rheumatoid arthritis - Hiroshi Tsushima; Shinji Morimoto; Maki Fujishiro; Yuko Yoshida; Kunihiro Hayakawa; Takuya Hirai; Tomoko Miyashita; Keigo Ikeda; Ken Yamaji; Kenji Takamori; Yoshinari Takasaki; Iwao Sekigawa; et al. (Taylor & Francis Group, 2017)
We have previously shown that the inhibition of connective tissue growth factor (CTGF) is a potential therapeutic strategy against rheumatoid arthritis (RA). CTGF consists of four distinct modules, including the insulin-like growth factor binding protein (IGFBP). In serum, insulin-like growth factors (IGFs) bind IGFBPs, interact with the IGF-1 receptor (IGF-1 R), and regulate anabolic effects and bone metabolism. We investigated the correlation between IGF-1 and the pathogenesis of RA, and the inhibitory effect on osteoclastogenesis and angiogenesis of the small molecular weight kinase inhibitor of the IGF-1 R, NVP-AEW541, against pathogenesis of RA in vitro. Cell proliferation was evaluated by cell count and immunoblotting. The expression of IGF-1 and IGF-1 R was evaluated by RT-PCR. Osteoclastogenesis was evaluated using tartrate-resistant acid phosphatase staining, a bone resorption assay, and osteoclast-specific enzyme production. Angiogenesis was evaluated by a tube formation assay using human umbilical vein endothelial cells (HUVECs). The proliferation of MH7A cells was found to be inhibited in the presence of NVP-AEW541, and the phosphorylation of extracellular signal-regulated kinase (ERK) and Akt was downregulated in MH7A cells. IGF-1 and IGF-1 R mRNA expression levels were upregulated during formation of M-colony stimulating factor (M-CSF) and receptor activator of NF-κB ligand (RANKL)-mediated osteoclast formation. Moreover, osteoclastogenesis was suppressed in the presence of NVP-AEW541. The formation of the tubular network was enhanced by IGF-1, and this effect was neutralized by NVP-ARE541. Our findings suggest that NVP-AEW541 may be utilized as a potential therapeutic agent in the treatment of RA.